Pengaruh Flexible Work Arrangement dan Kepuasan Kerja Terhadap Work Commitment Driver Grab Bike di Kota Medan - Malikasnah Lubis, Siti; Harahap, Kartini; Marakali Siregar, Onan (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Grab is a transportation technology service company that aims to improve the welfare of its workers. The problem is that flexible time and place, as well as job satisfaction that does not match the wages they earn, causes some Grab bike drivers to work not just for one partner but with two partners to meet the drivers' living needs. This research aims to analyze the influence of flexible work arrangements and job satisfaction on the work commitment of Grab bike drivers in the city of Medan. The form of this research is quantitative with a sample size of 96 respondents carried out using accidental sampling techniques. Primary data in this research was obtained by distributing questionnaires directly and secondary data was obtained through literature study. The results of this research show that flexible work arrangements (X1) and job satisfaction (X2) have a significant effect, both partially and simultaneously, on the work commitment of Grab bike drivers in Medan City. The coefficient of determination test shows that there is a close relationship between flexible work arrangements and job satisfaction with work commitment with an R value of 0.754. Through the adjusted R square value, it is also known that the flexible work arrangement and job satisfaction variables contribute 55.5% to the work commitment variable while the remaining 44.5% is influenced by other variables outside this research model.